2005
DOI: 10.1038/sj.bjc.6602451
|View full text |Cite
|
Sign up to set email alerts
|

The R72P P53 mutation is associated with familial breast cancer in Jewish women

Abstract: -Aviv University, Ramat Aviv Tel Aviv, Israel BRCA1/BRCA2 mutations account for a substantial proportion of familial breast cancer, but clearly mutations in additional genes exist, one candidate being the p53 gene. To evaluate its putative involvement in inherited predisposition to breast/ovarian cancer in Jewish high-risk women, mutational analysis of the p53 gene (exons 4 -9) was carried out using exon-specific polymerase chain reaction followed by denaturing gradient gel electrophoresis (DGGE) analysis, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 30 publications
1
49
2
1
Order By: Relevance
“…Keshava et al, 2002 were able to find a higher prevalence of the Arg allele in Caucasian women with breast cancer from New York, but not in Latin or African-American patients. Ohayon et al, 2005 studied jewish women with breast carcinoma, finding a higher prevalence of the Arg allele among Ashkenazi Jewish and Arab women (Alwadi et al, 2010), a high-risk population for breast cancer (Damin et al, 2006). Contradictory reports are also available in literature implicating that involvement of Arg/Pro heterozygous variant increases the risk of breast cancer from North Indian population.…”
Section: Discussionmentioning
confidence: 98%
“…Keshava et al, 2002 were able to find a higher prevalence of the Arg allele in Caucasian women with breast cancer from New York, but not in Latin or African-American patients. Ohayon et al, 2005 studied jewish women with breast carcinoma, finding a higher prevalence of the Arg allele among Ashkenazi Jewish and Arab women (Alwadi et al, 2010), a high-risk population for breast cancer (Damin et al, 2006). Contradictory reports are also available in literature implicating that involvement of Arg/Pro heterozygous variant increases the risk of breast cancer from North Indian population.…”
Section: Discussionmentioning
confidence: 98%
“…63 There are several studies that suggest that one or the other allele could influence the occurrence or progression of cancer. 64,65 At present however the results are confusing and a better understanding of the role of these two alleles in the pathway will be important. Recently, a polymorphism in the promoter of the human MDM-2 gene has been identified (SNP309).…”
Section: Questions About the P53 Pathway In A Larger Contextmentioning
confidence: 99%
“…Several groups have reported an association between the R72 p53 variant (binds and inactivates p73 better) and increased risk for epithelial cancer, including gastric cancer and cancer of the breast (Langerod et al, 2002;Bonafe et al, 2003;Buyru et al, 2003;Ohayon et al, 2005), ovary (Pegoraro et al, 2002), esophagus (Kawaguchi et al, 2000), skin (Dokianakis et al, 2000;Bastiaens et al, 2001;Shen et al, 2003;De Oliveira et al, 2004), lung , bladder (Soulitzis et al, 2002), prostate (Henner et al, 2001), and larynx (Sourvinos et al, 2001). In other studies, however, authors have found the opposite correlation, instead demonstrating an association between the P72 (lesser apoptotic) variant and increased risk for other cancer types, including cancer of the thyroid (Granja et al, 2004), nasopharynx (Tsai et al, 2002a, b;Tiwawech et al, 2003), prostate (Suzuki et al, 2003), skin (Chen et al, 2003), urogenital region (Kuroda et al, 2003), and lung Fan et al, 2000;Zhang et al, 2003).…”
Section: The Codon 72 Polymorphismmentioning
confidence: 99%